Treatment of Von Willebrand Disease - Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2001)
In von Willebrand disease, there are two main options for the treatment of spontaneous bleeding episodes and for bleeding prophylaxis: desmopressin and transfusional therapy with plasma products. Desmopressin is the treatment of choice for most patients with type 1, who account for approximately 70 to 80 per cent of all cases with the disease. This non-transfusional hemostatic agent raises endogenous factor VIII and von Willebrand factor three- to fivefold and thereby transiently corrects both the intrinsic coagulation and primary hemostasis defects. In patients with the more severe type 3 and in the majority of those with type 2 desmopressin is not effective or is contraindicated, so that it is usually necessary to resort to plasma concentrates containing factor VIII and von Willebrand factor. Concentrates treated with virus inactivation methods should be preferred to cryoprecipitate because they are equally effective and perceived as safer.
Keywords: Desmopressin; factor VIII; von Willebrand disease; von Willebrand factor